Response Inhibition, Attention and Processing Speed in Male Athlete and Non-athlete Adolescents - Saeideh Ayoubi; Nazgol Behgam; Dena Sadeghi-Bahmani; Hora Heidari; Zhila Maghbooli; Sharareh Eskandarieh (Caspian Journal of Neurological Sciences)
Background: Executive functions (EFs) are essential in controlling thoughts, emotions, and behavior. Evaluating the effect of athletic activity on the EFs that lead to better quality of life and mental and physical health is essential. Objectives: This study aimed to compare the components of EFs, including response inhibition, attention, and processing speed among male adolescents. Materials & Methods: A multi-stage random sampling method was used among 48 athletes and 48 non-athlete male adolescents in Tehran City, Iran. Cognitive functioning was assessed by a series of cognitive measures, including the go/no-go task, integrated visual and auditory test (IVA) and Wechsler intelligence scale for children–the fourth edition. Results: The results revealed significant differences in response omission and reaction time between the two groups (P=0.01). Nonetheless, no significant discrepancy in response error and the number of response inhibitions was detected (P=0.50). Regarding attention, the differences in visual and auditory attention and most related elements containing vigilance and processing speed were found to be significant (P<0.05). Furthermore, the findings indicate that more athletic activities are associated with better processing speed among athletes (P=0.029). Conclusion: There is a significant relationship between the amount of regular athletic activities and better EFs in male athlete adolescents. Also, a significant difference was observed between the components of EFs in male athlete and non-athlete adolescents. The difference in reaction time in response inhibition, visual and auditory and vigilance in attention was stronger than other dimensions investigated between our study groups.